2011
DOI: 10.1017/s0014479711000810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Fertilizers on Nitrate Accumulation in Vegetables and Mineral Nitrogen in Tropical Soils of Morogoro, Tanzania

Abstract: Nitrogen (N) nutrition is a key factor for vegetable growth and yield. However, different rates of nitrogen fertilization may trigger different responses to vegetables. A survey was conducted to investigate the effect of soil fertility management practices on nitrate concentration in vegetables. The survey results were used to plan experiments on the effect of chicken and cattle manures on nitrate levels in Chinese cabbage (Brassica rapa) and amaranthus (Amaranthus cruentus) grown in Tanzania and the patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
2
6
1
Order By: Relevance
“…High pH and High NH 4 /NO 3 Ratio. In accordance with previous investigations, 26,27 the pH dw from plants supplied with organic fertilizers was higher than for plants receiving inorganic fertilizers. The higher root zone pH could be responsible for the lower fruit yield in the organic treatments because it influences root growth and nutrient solubility/availability and uptake.…”
Section: ■ Discussionsupporting
confidence: 92%
“…High pH and High NH 4 /NO 3 Ratio. In accordance with previous investigations, 26,27 the pH dw from plants supplied with organic fertilizers was higher than for plants receiving inorganic fertilizers. The higher root zone pH could be responsible for the lower fruit yield in the organic treatments because it influences root growth and nutrient solubility/availability and uptake.…”
Section: ■ Discussionsupporting
confidence: 92%
“…The overall amaranth yields in this study were slightly higher than those reported from a study by Baitilwake et al [45], who investigated the impact of different fertilization regimes on amaranth and spinach yield in Morogoro. The yields from the present study were also two times higher than those reported from a study by Mulandana et al [46] in South Africa.…”
Section: Discussioncontrasting
confidence: 87%
“…Manure applications were done a week before to allow for proper mineralization [57]. Sowing was done by mixing 10 g of amaranth seeds with 1 kg of sand to obtain uniform stands, and then broadcasted at a rate of 1 g of seeds per m 2 [45,58]. The first harvest was done 21 days after sowing, to remove mature leaves for sale and give space for young plants to grow to maturity.…”
Section: Amaranth Irrigation and Fertilization Experimentsmentioning
confidence: 99%
“…This integration has the potential to improve production and economics for small‐scale farmers because B . rapa chinensis is a common crop on rural farms in Tanzania (Baitilwake, De Bolle, Salomez, Mrema & De Neve ) and a preferred vegetable by producers and consumers because it is easy to cultivate, with a short growing period (Kalisz, Kostrzewa, Sękara, Grabowska & Cebula ), has a unique flavour, health benefits (Pant, Radovich, Hue & Miyasaka ), an attractive appearance (Thosaikham, Jitmanee, Sittipout, Maneetong, Chantiratikul & Chantiratikul ) and high market demand worldwide (Cartea, Francisco, Soengas & Velasco ). Furthermore, B .…”
Section: Introductionmentioning
confidence: 99%
“…One form of such integration is that involving African sharptooth catfish, Clarias gariepinus and Nile tilapia, Oreochromis niloticus polyculture integrated with Chinese cabbage Brassica rapa chinensis. This integration has the potential to improve production and economics for small-scale farmers because B. rapa chinensis is a common crop on rural farms in Tanzania (Baitilwake, De Bolle, Salomez, Mrema & De Neve 2012) and a preferred vegetable by producers and consumers because it is easy to cultivate, with a short growing period (Kalisz, Kostrzewa, Se z kara, Grabowska & Cebula 2012), has a unique flavour, health benefits (Pant, Radovich, Hue & Miyasaka 2012), an attractive appearance (Thosaikham, Jitmanee, Sittipout, Maneetong, Chantiratikul & Chantiratikul 2014) and high market demand worldwide (Cartea, Francisco, Soengas & Velasco 2010). Furthermore, B. rapa chinensis responds well to moist fertile soil and can be produced annually in the tropics under full sun conditions and it is one of the most productive leaf vegetables grown with an average edible leaf yield of 3577 g m À2 (Idris, Ali, Gayah, Hassan & Abidin 2011;Kalisz 2011;Wong, Tseng, Hsu, Lur, Mo, Huang, Hsu, Lee & Liu 2014).…”
Section: Introductionmentioning
confidence: 99%